The Role of Pharmacy Personnel in Ensuring Appropriate Diarrhea Self-Medication in an Agro-Coastal Community in Jember, Indonesia - Wardhani, Firdha Aprillia; Nur Sepdianto, Bagas; Rachmawati, Ema; Pontanar, Mae Quenie; Afifah Machlaurin (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2026)
Background: Self-medication for diarrhea is a common self-care practice because diarrhea is often perceived as a mild, self-limiting condition. However, its high prevalence in Indonesia, particularly in Jember Regency, raises concerns about inappropriate medicine selection and use, including the unsupervised use of prescription-only drugs such as loperamide and antibiotics. Pharmacists and pharmacy personnel play a key role in promoting safe and rational self-medication. Method: This cross-sectional study was conducted in 15 pharmacies in Agro-Coastal Jember from August 2025 to January 2026. Using purposive sampling, 200 eligible respondents were recruited. Data were collected using a structured questionnaire and analyzed using univariate analysis and Chi-square analysis with the contingency coefficient test to assess the significance and strength of the relationship between variables. Result: Most respondents were female (67%), aged 26–35 years (46.5%), had a senior high school education (71%), and had a monthly income of < IDR 2,500,000 (86%). Loperamide was the most frequently used medication (46.36%), and more than half of the medications used were prescription-only (53.18%). The appropriateness of diarrhea self-medication remained low for both medicine selection (46.8% appropriate) and medicine use (28.2% appropriate). A significant association was found between the role of pharmacists/pharmaceutical staff and the appropriateness of diarrhea self-medication (p < 0.05), although the strength of the relationship was weak (r = 0.233 and r = 0.184). Conclusion: In conclusion, diarrhea self-medication in the Agro-Coastal Jember community was still dominated by inappropriate medication practices. Strengthening pharmacy-based counseling in community pharmacy and service quality is essential to improve the safety and rational use of medicines in diarrhea self-medication.